Effect of cooling rate on strength and fracture surfaces of alpha brass casting - Haque, Md. Mohafizul; Ismail, Ahmad Faris (Trans Tech Publications, 2008)
Green sand casting and chill mould casting methods are representing the slow and fast cooling rates of the brass casting, respectively. The compositions of the raw material for this study were about Cu70 and Zn30, which falls under alpha (α) brass. Slow cooling rate casting shows coarse dendritric structures with large spacing between the dendrites. On the other hand, faster cooling rate casting shows finer grains with shorter dendrite spacing. The developed structure during solidification influences the properties of the cast samples. As grain size decreases, the strength of the cast brass increases; micro-porosity in the casting decreases and the tendency for the casting to fracture also decreases. However, the macro-examinations of fracture surfaces of these castings show the differences in the cast samples. Fracture surfaces of the sand cast specimen show larger dimples taking longer time to break indicating higher elongation. However, chill cast specimen shows smaller dimples and cleavage type fracture surface having higher strength and lower elongation.